Evaluation of LVEF with Changing left Ventricular Morphology in Hypertrophic Cardiomyopathy - Masum, Md Mohiuddin; Shahrear, Rayhan; Yesmin, Zinnat Ara; Nishat, Latifa; Banu, Laila Anjuman (University Heart Journal, 2019)
Background:Hypertrophic cardiomyopathy (HCM) is the most frequent type of cardiomyopathy. HCM is a disease of changing cardiac morphology that causes various form of cardiac dysfunction. HCM patients may remain asymptomatic and undiagnosed for a long time. If they become symptomatic, they commonly present with breathlessness, chest discomfort, and exertion. It is also responsible for the sudden cardiac death.Proper assessment of the functional status of the heart is required for proper management strategies of HCM. Objective: The objective of the study was to assess the IVS, PWT and LVEF in different cardiac phenotypes as well as to draw correlation among them. Materials and method:A descriptive cross-sectional study was undertaken on thirty-four adult Bangladeshi hypertrophic cardiomyopathy patients (thirty-one male, three female). The study was carried out in the Department of Anatomy, BSMMU. Diagnoses adult HCM patients were selected as study patients. Transthoracic echocardiography was done to assess the interventricular septal thickness (IVS), left ventricular posterior wall thickness (PWT) and left ventricular ejection fraction (LVEF). Result: The changes in the value of the left ventricular ejection fraction shows significant correlation with left ventricular posterior wall thickness,rather than the interventricular septal thickness. Conclusion:Though significant correlation between left ventricular ejection fraction and left ventricular posterior wall thickness was found, a large cohort study could be done to see the long term outcome of such correlation. University Heart Journal Vol. 15, No. 1, Jan 2019; 12-15